Propuesta de un plan de exportación de arroz colombiano con destino a Canadá (2021)
In this document, a compilation of literature is carried out as a methodology for the development of a plan to export Colombian rice to Canada, the incidence of this type of market within the economy of both countries was recognized and a documentary review was conducted with the objective of determining the economic and financial viability of the project, to generate a successful export strategy and achieve an increase in production in the agricultural sector.